Individual identification of sika deer (Cervus nippon) using short tandem repeat analysis for investigating illegal carcass disposal in Japan - Aki Tanaka; Reina Ueda; Chihiro Udagawa; Toshinori Omi; Yuko Kihara; Shin-ichi Hayama (PLoS ONE, 2025)
The population of Japanese sika deer (Cervus nippon) are controlled by hunting to prevent damage to various crops in many areas in Japan. Hunters are subsidized by submitting the tail to the local government; animal carcasses must be properly disposed of after the hunt, and abandonment of hunted deer in the field is prohibited by law. However, there have been many carcasses of sika deer being abandoned without proper disposal. In such cases, individual identification by DNA analysis is required to match the abandoned deer and submitted tail and identify the suspect. When identifying individual wildlife by DNA analysis, it is crucial to select appropriate markers that consider both the procedure of the analysis and the animal species. To evaluate availability of Short Tandem Repeat (STR) analysis for the identification of sika deer, this study aimed to construct an STR database for sika deer in Japan and to evaluate the discrimination power of STR markers, using an identification kit for a closely related species of cattle and STR markers of the sika deer. The results showed polymorphism at six STR loci from the Bovine Genotypes Panel 3.1 Kit and two STR markers for sika deer, suggesting that these loci may be useful for sika deer identification. The coincidence rate for the three STR loci (CSSM019, TGLA53, ETH10) was 7.63 × 10-⁴, which was considered sufficient for identification of the sika deer population. This study was the first to evaluate the availability of sika deer STR analysis for individual identification in Japan and was expected to have applications in crime scene and wildlife forensics.